2017
DOI: 10.18632/oncotarget.16617
|View full text |Cite
|
Sign up to set email alerts
|

FHL2 interacts with iASPP and impacts the biological functions of leukemia cells

Abstract: iASPP is an inhibitory member of apoptosis-stimulating proteins of p53 (ASPP) family, which inhibits p53-dependent apoptosis. iASPP was highly expressed in acute leukemia, inhibited leukemia cells apoptosis and promoted leukemogenesis. In order to clarify its mechanism, a yeast two-hybrid screen was performed and FHL2 was identified for the first time as one of the binding proteins of iASPP. FHL2 was highly expressed in K562 and Kasumi-1 cells. FHL2 and iASPP interacted with each other and co-localized in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Indeed, there is growing evidence that overexpression, rather than mutation, of iASPP conveys its oncogenic properties. In addition to our previous characterization in p53 wild-type breast cancer (32), elevated iASPP levels have recently been reported in multiple human cancers, including bladder cancer (63), non-small-cell lung cancer (64), ovarian clear cell carcinoma (65), colorectal cancer (66), and particularly in acute leukemia where p53 mutations are relatively rare (67, 68).…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, there is growing evidence that overexpression, rather than mutation, of iASPP conveys its oncogenic properties. In addition to our previous characterization in p53 wild-type breast cancer (32), elevated iASPP levels have recently been reported in multiple human cancers, including bladder cancer (63), non-small-cell lung cancer (64), ovarian clear cell carcinoma (65), colorectal cancer (66), and particularly in acute leukemia where p53 mutations are relatively rare (67, 68).…”
Section: Discussionmentioning
confidence: 69%
“…Based on the functional diversity of LIM structural domains, FHL2 can interact with various proteins and thus play an important role in cell proliferation, differentiation, and signaling [ 74 , 75 ]. Findings suggest that the interaction of FHL2 and iASPP inhibits apoptosis and promotes cell proliferation [ 76 ]. If FHL2 is knocked out, then it causes the cell cycle to stay in the G0/G1 phase, thereby inhibiting cell proliferation [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…These same variants are in LD and have additionally been associated with myelopoiesis and hematopoiesis [69]. As indicated above, FHL2 is often encountered in the context of oncology, and a large body of research implicates FHL2 in the development of leukemia [69][70][71][72][73]. Several of these studies showed that increased FHL2 expression correlates with poor prognosis of leukemia [69,70].…”
Section: Fhl2 Snps In Coagulation and Cancermentioning
confidence: 95%